Targeting ETosis by miR-155 inhibition mitigates mixed granulocytic asthmatic lung inflammation - Kim, Ji Young; Stevens, Patrick; Karpurapu, Manjula; Lee, Hyunwook; Englert, Joshua A.; Yan, Pearlly; Lee, Tae Jin; Pabla, Navjot; Pietrzak, Maciej; Park, Gye Young; Christman, John W.; Chung, Sangwoon (Frontiers in Immunology, 2022)
Asthma is phenotypically heterogeneous with several distinctive pathological mechanistic pathways. Previous studies indicate that neutrophilic asthma has a poor response to standard asthma treatments comprising inhaled corticosteroids. Therefore, it is important to identify critical factors that contribute to increased numbers of neutrophils in asthmatic patients whose symptoms are poorly controlled by conventional therapy. Leukocytes release chromatin fibers, referred to as extracellular traps (ET) consisting of double-stranded (ds) DNA, histones, and granule contents. Excessive components of ET contribute to the pathophysiology of asthma; however, it is unclear how ET drives asthmatic phenotypes and whether it could be a potential therapeutic target. We employed a mouse model of severe asthma that recapitulates the intricate immune responses of neutrophilic and eosinophilic airway inflammation identified in patients with severe asthma. We used both a pharmacologic approach using miR-155 inhibitor-laden exosomes and genetic approaches using miR-155 knockout mice. Our data show that ET are present in the bronchoalveolar lavage fluid of patients with mild asthma subjected to experimental subsegmental bronchoprovocation to an allergen and a severe asthma mouse model, which resembles the complex immune responses identified in severe human asthma. Furthermore, we show that miR-155 contributes to the extracellular release of dsDNA, which exacerbates allergic lung inflammation, and the inhibition of miR-155 results in therapeutic benefit in the severe asthmatic mice. Our findings show that targeting dsDNA release represents an attractive therapeutic target for mitigating neutrophilic asthmatic phenotype, which is clinically refractory to the standard care.